Factors involved in specific transcription by mammalian RNA polymerase II: purification and analysis of transcription factor IIA and identification of transcription factor IIJ. - Cortes, P (1992)
The previously described transcription factor IIA (TFIIA) protein fraction was separated into two factors that affect transcription, TFIIA and TFIIJ. TFIIA was found to have a stimulatory effect, and TFIIJ was found to be required for transcription. The requirement of TFIIJ was observed when bacterially produced purified human or yeast (Saccharomyces cerevisiae) TATA-binding protein (TBP) was used in lieu of the endogenous HeLa cell TFIID complex, suggesting that TFIIJ may be part of the TFIID complex. The stimulatory activity of TFIIA was found also to be dependent on the source of the TBP. Transcription reactions reconstituted with TFIID were stimulated by TFIIA; however, when human or yeast TBP was used instead of TFIID, TFIIA had no effect. TFIIA was found to interact with the TBP and was extensively purified by the use of affinity chromatography on columns containing immobilized recombinant yeast TBP. TFIIA is a heterotrimer composed of polypeptides of 34, 19, and 14 kDa. These three polypeptides were required to isolate, by using the gel mobility shift assay, a stable complex between TBP and the TATA box sequence.